Features of the functioning of organism energy subsystem by indicators of cardiovascular system among individyals prone and resistant to development of the monotony state - Kalnysh, V.; Pyshnov, G.; Opanasenko, V.; Ogryzkov, A. (Environment & Health, 2016)
In connection with the need to manage complex automated processes, the problem of study of the state of monotony in the operator's activity is quite actual today.The goal was the revealing of features of the energy supply of the human body when making long-term monotonous work among individuals inclined and resistant to the development of the state of monotony.Materials and methods. In studies 155 volunteers took part, who were tested by monotonous information load modeling (by computer) operator activity.Results. In indexes of the cardiovascular system activity it is revealed that the energy supply of the body during performing monotonous work among people resistant and prone to the development of the state of monotony is going by fundamentally different mechanisms. Individuals who are prone to the development of the state of monotony, hemodynamic changes have a pronounced phase character, what may indicate on the disadaptation and raise the physiological cost of work in the formation of the state of monotony.Conclusions. A feature of the regulation of the energy supply of monotonous activity among individuals resistant to the development of monotony, is the harmonious relations of the sympathetic and parasympathetic divisions of the autonomic nervous system against the background of relatively high activation of cardiovascular system.Tags: monotony, monotonous work, functional status, cardiovascular system, the energy supply of activity.
Keywords: monotony; monotonous work; functional state of cardiovascular system; energy supply of activity